SEMANTIC SHIFT IN THE ENGLISH-INDONESIAN TRANSLATION OF TINTIN COMIC SERIES Ã¢â‚¬Å“THE ADVENTURES OF TINTIN: THE BLACK ISLANDÃ¢â‚¬Â - Agustine, Diar Ajeng (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2014)
This article is about semantic shift found in the English-Indonesian translation of Tintin comic series Ã‚Â´Ã¢â‚¬â„¢The adventure of Tintin: The Black IslandÃ¢â‚¬Â. The main purposes of this study are to analyze the categories of semantic shift; generalization, specification, substitution, reversal, deviation, and its manifestation found in the object of the study. Descriptive qualitative method is used in conducting this research.Ã‚Â  The writer found 60 data in the object study. They are substitution 33 data (55%), specification 11 data (18,3%), generalization 6 data (10%), reversal 6 data (10%), and deviation 4 data (6,7%). In the end, the writer hopes that this research could help readers who are interested in translation, especially ones who intend to learn further about semantic shift in translation. Furthermore, this research is expected to improve the ability in analyzing English as a source language text and Indonesian target language text, especially for those who are interested in translation.